A Study On Spectral And Statistical Analysis Of Noisy Signals For Physical Processes - Kaynaş, Tayfun; Şeker, Serhat (İstanbul Kültür Üniversitesi Yayınları, 2006)
In this study, it is considered a sinusoidal signal with is third harmonic as well as the fundamental frequency adding the noise term, which is produced using a Gaussian random number generator. Hence spectral and statistical properties of this signal are examined and Signal-to-Noise Ratio (SNR) is computed comparing with the probability function of the noisy signal.
Keywords: power spectrum; statistical parameters; harmonics; Gaussian noise; güç spektrumu; istatistiksel parametreler; harmonikler; Gauss gürültüsü